Human Supernumerary Teeth-Derived Apical Papillary Stem Cells Possess Preferable Characteristics and Efficacy on Hepatic Fibrosis in Mice. (30th January 2020) - Yao, Jun; Chen, Nan; Wang, Xiaojing; Zhang, Leisheng; Huo, Jiali; Chi, Ying; Li, Zongjin; Han, Zhongchao
Abstract : Dental tissue has been acknowledged as an advantaged source for high-quality dental pulp stem cell (DPSC) preparation. However, despite the accomplishment of the separation of DPSCs from permanent teeth and supernumerary teeth, the deficiency of rigorous and systematic clarification on the signatures and efficacy will hinder their prospects in regenerative medicine. In this study, we primitively isolated permanent teeth-derived DPSCs and supernumerary teeth-derived apical papillary stem cells (SCAP-Ss) with parental consent. Immunophenotype of DPSCs and SCAP-Ss was determined by a flow cytometry assay, and the cell viability was verified by multidimensional detections including cell proliferation, cell cycle, apoptosis, and senescence. The migration and clonogenic capacity were examined by a wound healing test and crystal violet staining, respectively. The multilineage differentiation potential was quantitated by utilizing Oil Red O staining and Alizarin Red staining, together with real-time PCR analysis. The efficacy on a mouse hepatic fibrosis model was evaluated by using histologic sections and liver function tests. Herein, we showed that SCAP-Ss exhibited comparable immunophenotype and adipogenic differentiation capacity as DPSCs. However, different from DPSCs, SCAP-Ss exhibited superiority in cell viability and osteogenic differentiation. Simultaneously, injection of DPSCs and SCAP-Ss significantly reduced inflammatory infiltration, enhanced liver-associated gene expression, and finally relieved symptoms of hepatic fibrosis. In conclusion, SCAP-Ss possess preferable characteristics and efficacy on hepatic fibrosis in mice. Our findings suggest that SCAP-Ss are an easily accessible postnatal stem cell source with multifaceted characteristics for regenerative medicine.